Depicting ‘Natural’ Disasters in U.S.-American History and Culture: San Francisco’s City Hall as an Icon of the 1906 Earthquake and Fire - Leikam, Susanne (Current Objectives of Postgraduate American Studies, 2012)
The article examines the role that visual representations of San Francisco’s first City Hall played in the aftermath of the 1906 Earthquake and Fire. Not only did they offer a projection screen for the collective trauma but they also provided a starting point for recollection and re-enactment. With the City Hall vicinity as an example, it is further shown that what was perceived at the time as nature’s obliteration of the metropolis was rather a man-made disaster.